Influence of drivers’ visual and cognitive attention on their perception of changes in the traffic environment - Tina Cvahte Ojsteršek; Darja Topolšek (European Transport Research Review, 2019)
Abstract Drivers are met with numerous elements requiring their attention while driving. The present research focuses on selected visual and cognitive distractions that the driver is faced with, and on their influence on detecting and perceiving changes in the traffic environment. Driver self evaluation data was used to define which elements attract most visual and cognitive distraction. A constructed conceptual model was subjected to analysis using Exploratory factor analysis (EFA), Confirmatory factor analysis (CFA), and Structural Equation Modelling (SEM). Main findings show that thinking about personal problems, chores and errands as well as roadside advertisements on the cognitive side, and looking at advertisements and the natural environment on the visual side, present the most negative impacts on drivers’ perception of crucial changes in the traffic environment. On the other hand, drivers that visually focus on traffic signals and pedestrians and think about driving speed, driving rules, and other traffic participants, tend to notice crucial changes in the traffic environment more often.